If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(x+1)=5(2x+2)
We move all terms to the left:
3(x+1)-(5(2x+2))=0
We multiply parentheses
3x-(5(2x+2))+3=0
We calculate terms in parentheses: -(5(2x+2)), so:We get rid of parentheses
5(2x+2)
We multiply parentheses
10x+10
Back to the equation:
-(10x+10)
3x-10x-10+3=0
We add all the numbers together, and all the variables
-7x-7=0
We move all terms containing x to the left, all other terms to the right
-7x=7
x=7/-7
x=-1
| 5x+4+8x-3+49=180 | | 8=-4(x–1) | | 2/4x-15=-5 | | x2.5=1.2 | | 4y+y-5=180 | | 9x+7=−43 | | 83=10b+3 | | -12+14+3x=2x+2 | | 16=6(x-5)-4x | | 2x+3=x+2+x | | 5x-43+4x=38 | | −23−16x+12=−9 | | k4+14=16 | | 2.5•5x=17 | | k4+ 14=16 | | 2=–(d+–15) | | 2.5x5x=17 | | 6(2x+5)=-54 | | −23(−16x+12)=−9 | | 2x²-1=4x | | -0.75(4x+6)-x=10-2x | | 2x+26=3 | | 2w+21=48 | | 4=p/4-1 | | 2x+25+x+19=3 | | 16+8y=72 | | 1-(2x+4=-4+5 | | k=8k=28= | | -8.7+9.9z=-3.5 | | -3x+6=-3(2x+4) | | 16+8y=73 | | -10-g/2=14 |